Antimicrobial activity of ceftazidime-avibactam and comparators against Pseudomonas aeruginosa and Enterobacterales collected in Croatia, Czech Republic, Hungary, Poland, Latvia and Lithuania: ATLAS Surveillance Program, 2019 - Adámková, V; Mareković, I; Szabó, J; Pojnar, L; Billová, S; Horvat Herceg, S; Kuraieva, A; Możejko-Pastewka, B (European journal of clinical microbiology & infectious diseases, 2022)
Antimicrobial susceptibility of clinical isolates collected from sites in central Europe in 2019 was tested by CLSI broth microdilution method and EUCAST breakpoints. Most active were amikacin, ceftazidime-avibactam and colistin; respectively, susceptibility rates among P. aeruginosa (n = 701) were 89.2%, 92.2% and 99.9%; difficult-to-treat (DTR) isolates, 62.5%, 37.5% and 100%; multidrug-resistant (MDR) isolates, 68.3%, 72.9% and 99.5%; meropenem-resistant (MEM-R), metallo-β-lactamase-negative (MBL-negative) isolates, 72.8%, 78.6% and 100%. Among Enterobacterales (n = 1639), susceptibility to ceftazidime-avibactam, colistin and tigecycline was ≥ 97.9%; MDR Enterobacterales, 96.8%, 94.4% and 100%, respectively; DTR isolates, ≥ 76.2% to ceftazidime-avibactam and colistin; MEM-R, MBL-negative isolates, ≥ 90.0% to ceftazidime-avibactam and colistin.
Keywords: meropenem; Enterobacteriaceae; kolistin; Drug Combinations; Enterobacterales; Difficult-to-treat; Poland; Česká republika; ceftazidim; antibakteriální látky; Microbial Sensitivity Tests; Croatia; Lotyšsko; Antimicrobial surveillance; Litva; Czech Republic; Maďarsko; azabicyklické sloučeniny; lidé; Pseudomonas aeruginosa; Anti-Bacterial Agents; ATLAS; Humans; Meropenem; mikrobiální testy citlivosti; Ceftazidime; Hungary; Lithuania; Chorvatsko; Colistin; Latvia; Polsko; fixní kombinace léků; Ceftazidime-avibactam; Azabicyclo Compounds